2010
DOI: 10.1038/pcan.2010.4
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of serum testosterone on urinary continence and sexual activity in patients undergoing radical prostatectomy for clinically localized prostate cancer

Abstract: The aim of the present study was to evaluate how serum testosterone level (T) can affect urinary continence and erectile function in patients undergoing radical prostatectomy (RP). We included 257 patients with clinically localized prostate cancer, those who had filled out preoperative quality of life questionnaires (University of California, Los Angeles Prostate Cancer Index, International Index of Erectile Function (IIEF)), and those who had T and total PSA sampled the day before surgery. We calculated corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…([46], EBMl3b) that in men with SD and no apparent prostate disease serum PSA is significantly correlated with serum T only in younger men, and in the first decile of T concentrations, and does not increase for serum concentrations above the level of 8 to 10 nmol/L (2.32 to 2.88 ng/mL) suggest a saturation level higher than that proposed by Morgentaler and Traish [165]. The same group also reported that in men with actual PCa, PSA was correlated with T only below the level of 10.4 nmol/L (3 ng/mL) ([172], EBMl3b). Lastly, in another population of men with localized PCa, no correlation between PSA and any of 5 different androgens was found, while following 6 months of ADT, a significant correlation was observed between PSA and the five androgens (T and DHT, but also DHEA‐S and androstenedione) ([173], EBMl2b).…”
Section: Treatment Of Tdmentioning
confidence: 87%
“…([46], EBMl3b) that in men with SD and no apparent prostate disease serum PSA is significantly correlated with serum T only in younger men, and in the first decile of T concentrations, and does not increase for serum concentrations above the level of 8 to 10 nmol/L (2.32 to 2.88 ng/mL) suggest a saturation level higher than that proposed by Morgentaler and Traish [165]. The same group also reported that in men with actual PCa, PSA was correlated with T only below the level of 10.4 nmol/L (3 ng/mL) ([172], EBMl3b). Lastly, in another population of men with localized PCa, no correlation between PSA and any of 5 different androgens was found, while following 6 months of ADT, a significant correlation was observed between PSA and the five androgens (T and DHT, but also DHEA‐S and androstenedione) ([173], EBMl2b).…”
Section: Treatment Of Tdmentioning
confidence: 87%
“…This explanation would also justify the increased gonadotropin levels observed with the normal Te levels in previous studies at 6 and 12 months following RP (9,12). In addition to possessing significance in endocrinological terms, the fluctuation of the Te levels in the first 3 months following RP may be important from a clinical perspective, since this period of time has critical relevance in the recovery of urinary continence and potency (21), and the resultant Te levels are significantly involved in the recovery of these functions (4,5). Although the present study did not record data on the functional recovery of these patients, we suggest that future investigations into the correlation between functional recovery and sex hormones should focus on the first months after prostatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The serum level of testosterone (Te) may affect sexual function in males treated by radical prostatectomy (RP) for clinically localized prostate cancer (PCa) (3). It has been suggested that Te may also affect urinary continence and increase bladder compliance following RP, with a relaxing effect in smooth muscle bladder cells through the nitric oxide synthase/nitric oxide pathway (4,5). Moreover, certain authors have reported a significant correlation between Te levels and adverse pathological features and biochemical recurrence, even though the prognostic value of pre-operative Te remains unclear (67).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the hypogonadism in the elderly or during androgen deprivation therapy impairs urinary function [22]. Gacci et al [23] evaluated how serum testosterone affected urinary continence in 257 patients who underwent RRP. They found a strong association between urinary continence and sexual potency in eugonadal patients and the lack of this correlation in hypogonadal men.…”
Section: Discussionmentioning
confidence: 99%